FROM POLICY TO MISERY? THE STATE AGRICULTURAL FARMS VS. ‘THE RURAL’ - Biegańska, Jadwiga; Dymitrow, Mirek; Grzelak-Kostulska, Elżbieta (Quaestiones Geographicae, 2019)
1989 was a turning point in the socio-economic development in the former Eastern bloc, initiating a systemic transformation that affected the society at large. It also contributed to the crystallisation of certain cultural landscapes, hitherto largely illegible due to the inhibition of spatial processes encountered during socialism. In Poland, after a quarter-century of a free market economy, the focus on social problems began to expand to the spatial realm as well. It became apparent that the progressive social polarisation that followed was most prominent in environments striated by a particular landscape type – the former State Agricultural Farm (PGR). Considering PGRs as ‘the epitome of rurality’ subject to ideas informing about the direction of contemporary ‘rural development’ prompts a different way of looking at the problem. In this paper, we investigate the concept of rurality in the discursive tenor of implemented policy and contrast it with contextualised empirical examples. Our findings suggest that an efficient policy should be confronted with the expectations of residents at the local level, and introducing top-down actions usually ends in failure as in the case of post-PGR estates.